A framework for the management of donated medical devices based on perspectives of frontline public health care staff in Ghana. Issue 1 (September 2020) - Williams, Dinsie B; Kohler, Jillian C; Howard, Andrew; Austin, Zubin; Cheng, Yu-Ling
Background: Transnational funders provide up to 80% of funds for medical devices in resource-limited settings, yet sustained access to medical devices remains unachievable. The primary goal of this study was to identify what factors hinder access to medical devices through the perspectives of frontline public hospital staff in Ghana involved in the implementation of transnational funding initiatives. Methods: A case study was developed that involved an analysis of semi-structured interviews of 57 frontline technical, clinical and administrative public health care staff at 23 sites in Ghana between March and April 2017; a review of the national guidelines for donations; and images of abandoned medical devices. Results: Six key themes emerged, demonstrating how policy, collaboration, quality, lifetime operating costs, attitudes of health care workers and representational leadership influence access to medical devices. An in-depth assessment of these themes has led to the development of an enterprise-wide comprehensive acquisition and management framework for medical devices in the context of transnational funding initiatives. Conclusion: The findings in this study underscore the importance of incorporating frontline health care staff in developing solutions that are targeted at improving delivery of care. Sustained access to medical devices may be achieved in Ghana through the adoption of a rigorous and comprehensive approach to acquisition, management and technical leadership. Funders and public health policy makers may use the study's findings to inform policy reform and to ensure that the efforts of transnational funders truly help to facilitate sustainable access to medical devices in Ghana.